Performance Pheretima sp. and The Quality of Vermicompost on Media Using Clam and Snail Shell Flour (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
The abundance of green mussel shells, clam shells, and snail shells that have not been maximally utilized has caused environmental disturbances. These shells can be used as a substitute for worm food because of their good nutritional content. This research aimed to analyze the productivity of Pheretima sp. with the combination of shell powder (green mussel, clam, and snail) and cow dung to their living media (feed) and the quality of vermicompost. The data were analyzed using SAS Studio application with completely randomized design (CRD), 10 treatment levels, with 3 replications each. The observed variables included earthworm productivity, vermicompost quality, and vermicompost performance. The results of the studyshow a significant (P